Analisis faktor-faktor yang mempengaruhi laba bersih Bank Umum Syariah di Indonesia - Rabiat El Adawiya (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2020)
The goal of this study was to ascertain whether the variables examined have an effect on net income. Expected Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income (BOPO), Third Party Funds (DPK), Financing to Deposit Ratio (FDR), and Non-Performing Financing are all factors that affect net income (NPF). The study was undertaken at Bank Muamalat Indonesia (BMI), Bank Syariah Mandiri (BSM), Bank Syariah Mega Indonesia (BSMI), and Bank BRISyariah (BRIS), with the report being published quarterly. The regression technique employed is panel data regression. The investigation revealed that between 2009 and 2012, BOPO and DPK had a considerable impact on net profit, with an adj R-squared level of 80.87 percent. While the variables CAR, FDR, and NPF had no effect on net income between 2009 and 2012.